Predicting overt and covert antisocial behaviors: parents, peers, and homelessness - Tompsett, Carolyn J. (2010)
Parental deviance, parental monitoring, and deviant peers were examined as predictors of overt and covert antisocial behaviors. Homeless (N=231) and housed (N=143) adolescents were assessed in adolescence and again in early adulthood. Homelessness predicted both types of antisocial behaviors, and effects persisted in young adulthood. Parental deviance predicted only overt antisocial behaviors in adolescence, and was fully mediated by parental monitoring. Parental monitoring predicted both types of antisocial behaviors in adolescence, and was partially mediated by peer deviance. Parenting and peer influences did not consistently predict antisocial behaviors in adulthood.